Money Management Behavior and Issues among Congolese University Students: Requirement for Educational Finance - Vigoureux Chinyabuuma; Suprapto Suprapto; Muhammad Imron Romadhon (Jurnal Economia, 2020)
Abstract: This study investigated the factors that influence a number of financial issues students face in the Democratic Republic of Congo. A survey was conducted to collect the data for this study. Respondents were asked to demonstrate which of the ten financial education topics they were keen on taking. Descriptive statistics was utilized to present the data. The results show that loans, residential status, and impulse spending were the causes that brought about the students’ financial issues. By identifying the causes of students’ financial issues, educators may be able offer a course, in which students can learn the money management skills needed to address these issues. The respondents were asked if they would be interested in financial education if offered. Almost all of the students expressed their interest in learning how to manage their money. In conclusion, many of the respondents did not have sufficient knowledge and skills in managing their financial affairs.Keywords: financial issues, loans, residential status, impulse spending, money management Perilaku dan Masalah Pengelolaan Uang di Kalangan Mahasiswa Universitas Kongo: Kebutuhan Keuangan PendidikanAbstrak: Penelitian ini menyelidiki faktor-faktor yang mempengaruhi sejumlah masalah keuangan yang dihadapi siswa di Republik Demokratik Kongo. Sebuah survei dilakukan untuk mengumpulkan data untuk penelitian ini. Responden diminta untuk menunjukkan yang mana dari sepuluh topik pendidikan keuangan yang mereka minati. Statistik deskriptif digunakan untuk menyajikan data. Hasil penelitian menunjukkan bahwa pinjaman, status tempat tinggal, dan pengeluaran impulsif merupakan penyebab yang menimbulkan masalah keuangan siswa. Dengan mengidentifikasi penyebab masalah keuangan siswa, pendidik mungkin dapat menawarkan kursus, agar siswa dapat mempelajari keterampilan pengelolaan uang yang diperlukan untuk mengatasi masalah ini. Para responden ditanya apakah mereka akan tertarik dengan pendidikan keuangan jika ditawarkan. Hampir semua siswa menyatakan minatnya untuk mempelajari cara mengelola uang mereka. Kesimpulannya, banyak responden yang tidak memiliki pengetahuan dan keterampilan yang memadai dalam mengelola urusan keuangannya.Kata Kunci: masalah keuangan, pinjaman, status tempat tinggal, pengeluaran impulsif, pengelolaan uang